Menelusuri Akar Konflik Antaretnik - Arkanudin, Arkanudin (Mediator, 2006)
Ethnical conflicts has become one of main problems existed in multiethnic countries like Indonesia. In West Kalimantan, at least 10 ethnical conflict between Dayak and Madura are recorded from 1933 to 1977. The conflict reached a highly escalating stage when people get killed in the accidents. This article explores violence culture featured on the conflict. Both Dayak and Madura are famously known as tough, temperamental, and hard-determined people. Unfair political measures are believed as the source of the conflict as well as different cultural values, cultural beliefs, and cultural orientations.